Optimization of extraction conditions of antioxidant phenolic compounds from mashua (Tropaeolum tuberosum Ruíz & Pavón) tubers - Chirinos R. (2007)
We thank Dr. Carlos Arbizu, International Potato Center (Lima, Peru) for providing the mashua genotypes. This research was supported by the CUI project of the Cooperation Universi- taire au Developpement (CUD, Belgium), and by the Consejo Nacional de Ciencia y Tecnolog´ıa (CONCYTEC, Peru).